Environmental education: a panacea for safe and healthy primary school environment in Nigeria (2015)
The primary school environment, just like other school environment should be the safest for both staff and pupils. But, this is not always the case in most Nigerian public primary schools as accidents and injuries are reported due to the poor conditions of the school environment especially the playground and classrooms. Indeed other components of the school environment are also associated with injuries which contradict the importance of safe school environment. This paper defines environment health and accentuated the need to reduce injuries related to the school environment through environmental education especially among primary school pupils. This will serve as a way of enhancing their awareness of the various dangers in and around the school environment including man-made and natural environmental degradation. The paper also considered environmental education as a multidisciplinary subject with the sole objective of creating a school environment that will evoking pupils sense of inclusion, physical and psychological safety and by creating positive, friendly and safe school environment through collaboration between the school and all sections of the society. The expectant result will lead to the development of healthy and safe environmental ethics and increase the value placed on conservation of life and environmental safety. The paper recommended that pupils should be adequately equipped with the necessary manipulative skills that will help them pay attention to both the physical and social environment that promotes safety, healthy interpersonal relationships, and freedom from discrimination and abuse.